ANALISIS HUKUM TERHADAP PEMIDANAAN ANAK SEBAGAI PELAKU TINDAK PIDANA PENCABULAN (Studi Putusan Nomor 6/Pid.Sus.Anak/2016/PN.Mbn) - Arifman Febriyanto Saputra Zamili (Jurnal Panah Hukum, 2022)
Child punishment often has a legal conflict between the application of applicable law and the interests of children's rights and obligations in law. Children who commit a criminal act should be examined and judged by considering things that can change psychology without having to apply imprisonment to children. This research uses normative legal research with data collection techniques using secondary data consisting of primary, secondary and tertiary legal materials. In the results of the study, children were sentenced to imprisonment due to not achieving diversion due to the threat of punishment for the actions of children more than 7 (seven) years. The researcher's suggestion is that the judge in the process of punishing children as perpetrators of criminal acts of obscenity must pay attention to the interests of children according to applicable laws and the government as lawmakers must strictly regulate the issue of punishing children, so that the rights of the child can be protected by law